Activities and performance in export of the foreign exchange operation of National Bank Ltd. (NBL), Banani branch - Sultana, Shereen (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Master of Business Administration, 2015.